Does physical activity protect older persons with frailty and cognitive impairment from excess all-cause mortality?. (November 2021) - Li, Chia-Lin; Chiu, Yu-Chan; Shyu, Yea-Ing L.; Stanaway, Fiona F.; Chang, Hsing-Yi; Bai, Yuh-Bin
Highlights: Inactivity, frailty and cognitive impairment jointly increase risk of mortality. Being active is associated with lower mortality in those frail/pre-frail alone. Being active is associated with lower mortality in those cognitively impaired alone. Abstract: Objectives: The main aim of this study was to examine how physical activity in combination with physical frailty and cognitive impairment affects risk of mortality in older adults. Study Design: A national sample of community-dwelling Taiwanese aged 65 years or older (n=2678) was followed for 5 years. Main outcome measures: Frailty was determined based on the Fatigue, Resistance, Ambulation, Illness, and Loss of weight (FRAIL) scale. The Mini-Mental State Examination was used to assess cognitive impairment. Information on self-reported physical activity was collected at baseline. The study cohort was followed until the date of death or the end of the study period (31 December 2018). Deaths were confirmed by the computerized data files of the National Register of Deaths. Results: A total of 417 deaths were recorded after 12415.2 person-years of follow-up. After adjustment for other factors, compared with active participants who were physically robust with normal cognition, inactive participants who were with either frail/pre-frail or cognitively impaired had hazard ratios for mortality of 2.65 (95% CI=[1.88-3.74]) and 3.09 (95% CI=[2.08-4.59]), respectively. Inactive participants with coexisting frailty/pre-frailty and cognitive impairment had the highest hazard ratio for mortality of 3.85 (95% CI=[2.73-5.45]). Being active was associated with a mortality reduction of 31%, 38%, and 42% in physically robust participants with normal cognition, those who were frail/pre-frail only, and those with cognitive impairment only, respectively. Conclusions: Having a physically active life style has beneficial effects on survival in older persons with either frailty/pre-frailty or cognitive impairment.